2021
DOI: 10.3390/life11070607
|View full text |Cite
|
Sign up to set email alerts
|

Chemical-Mediated Targeted Protein Degradation in Neurodegenerative Diseases

Abstract: Neurodegenerative diseases, including Alzheimer’s disease, Huntington’s disease, and Parkinson’s disease, are a class of diseases that lead to dysfunction of cognition and mobility. Aggregates of misfolded proteins such as β-amyloid, tau, α-synuclein, and polyglutamates are known to be among the main causes of neurodegenerative diseases; however, they are considered to be some of the most challenging drug targets because they cannot be modulated by conventional small-molecule agents. Recently, the degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…As ongoing therapies and clinical trials for cancer have been discussed in previous sections, here we will focus on interventions that could alleviate neurodegenerative diseases. The disparities between the pathophysiology of distinct proteinopathies led to exploring many different types of interventions for preventing protein aggregation (Arosio et al 2014 ; Hyun and Shin 2021 ; Lashuel 2021 ; Salahuddin et al 2021 ). Such interventions can be classified as antibodies, protein stabilizers, nanoparticles, sequestering monomers and small molecule inhibitors of aggregation.…”
Section: Clinical Trials On Proteolytic Systems To Prevent Protein Aggregationmentioning
confidence: 99%
“…As ongoing therapies and clinical trials for cancer have been discussed in previous sections, here we will focus on interventions that could alleviate neurodegenerative diseases. The disparities between the pathophysiology of distinct proteinopathies led to exploring many different types of interventions for preventing protein aggregation (Arosio et al 2014 ; Hyun and Shin 2021 ; Lashuel 2021 ; Salahuddin et al 2021 ). Such interventions can be classified as antibodies, protein stabilizers, nanoparticles, sequestering monomers and small molecule inhibitors of aggregation.…”
Section: Clinical Trials On Proteolytic Systems To Prevent Protein Aggregationmentioning
confidence: 99%
“…In this context, important progress has been made by adapting the UPS so as to target selected substrates and prevent PPIs [68]. A chimeric compound of E3 ubiquitin ligase and a SYN-binding motif may allow PD to be treated (Figure 5) [69]. This approach has been used to eliminate over-expressed SYN [70,71].…”
Section: Proteolysis Targeting Chimera (Protac) Technologymentioning
confidence: 99%
“…Below we give an overview of the ways PROTACs have recently been applied to Parkinson's disease. 7,8 Parkinson's disease (PD) is a neurological disorder, whose pathological signatures are the degeneration of dopamine neurons and the formation of alpha-synuclein-enriched Lewy bodies. 9 Genetic studies of familial PD cases have identified mutations, duplications and triplications of α-synuclein and other risk loci.…”
Section: Ups-dependent Intracellular Protein Degradation Is Mediated ...mentioning
confidence: 99%
“…The field of PROTACs has evolved rapidly in recent years, encompassing numerous applications to neurodegeneration as well as other human diseases. Below we give an overview of the ways PROTACs have recently been applied to Parkinson's disease 7,8 …”
Section: Ups‐dependent Intracellular Protein Degradation Is Mediated ...mentioning
confidence: 99%